2007
DOI: 10.1016/j.juro.2007.01.113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inositol Hexaphosphate (Phytate) on Calcium Binding, Calcium Oxalate Crystallization and In Vitro Stone Growth

Abstract: Inhibition of crystallization by phytate does not depend on decreasing the effective ionized calcium concentration and inhibition of in vitro stone growth does not depend on inhibiting crystallization of the suspended crystals. To our knowledge this is the first demonstration of a quantitative distinction between the inhibition of crystallization and stone growth. Inhibition of in vitro stone growth in the presence of macromolecules occurred at concentrations consistent with urinary phytate excretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…While IP6 is a known inhibitor of calcium phosphate crystallization, [ 27,28 ] little is known about the inhibitory properties of IP6 on CaOx crystallization. [ 31 ] Thus, in a first step we investigated the effects of IP6 on CaOx crystallization in human urine, as well as the impact of chemical modifications on the in vitro CaOx growth inhibition efficacy of the molecule ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…While IP6 is a known inhibitor of calcium phosphate crystallization, [ 27,28 ] little is known about the inhibitory properties of IP6 on CaOx crystallization. [ 31 ] Thus, in a first step we investigated the effects of IP6 on CaOx crystallization in human urine, as well as the impact of chemical modifications on the in vitro CaOx growth inhibition efficacy of the molecule ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies reported that PA has beneficial effects on human health through its antioxidant (15), anticancer (16), and antidiabetic (17) effects. It can also protect against the development of Parkinson's disease (18) and renal calculi (19). However, PA has not been widely studied as a natural antimicrobial agent.…”
mentioning
confidence: 99%
“…The antioxidant activity of phytic acid is being studied in several areas, for example, in food preservation (Stodolak et al, 2007;Canan et al, 2012), oxidation of metals (Gupta et al, 2013), and in human health, with anticancer activity (Norazalina et al, 2010;Norhaizan et al, 2011), in the treatment of diabetes (Lee et al, 2006), renal calculus (Saw et al, 2007), and Parkinson's disease (Xu et al, 2008).…”
Section: Antioxidant Actionmentioning
confidence: 99%